Kepemimpinan Kiai dalam Mengembangkan Kurikulum Pendidikan di Pondok Pesantren: (Studi Kasus: Pondok Pesantren al-Rifaie 2 Gondanglegi, Pondok Pesantren Miftahul Ulum Putri Ganjaran, dan Pondok Pesantren Rakyat alAmin Malang) - Yazidul Busthomi (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract: The main capital that causes a Kiai to succeed indeveloping education in Islamic boarding schools is, in essence,extraordinary knowledge in his leadership in developing education inhis Islamic boarding school. So that education in Islamic boardingschools that are developing at this time is solely dependent on theleadership of the Kiai in developing his education. Based on thedescription of the problem, the researcher raised the title